Modified Xiaoyaosan reverses aberrant brain regional homogeneity to exert antidepressive effects in mice. Issue 2 (4th March 2019) - Bi, Yanmeng; Huang, Peng; Dong, Zhaoyang; Gao, Tingting; Huang, Shaohui; Gao, Lei; Lv, Zhiping
Abstract : The aim of this study is to explore the macroscale neural mechanisms of the antidepressant effects of Xiaoyaosan, a traditional Chinese herbal formula. We analyzed blood oxygen level‐dependent (BOLD) functional magnetic resonance imaging signals. To further minimize the hemodynamic variations of BOLD signals and analyze the intra‐region neural activity or temporal coherence, we employed the newly developed regional homogeneity (ReHo) approach to determine aberrant functional connectivity using the chronic unpredictable mild stress (CUMS) mouse model of depression and to also explore the brain‐region rescue effect of modified Xiaoyaosan (MXYS) in such mice. We found the aberrant ReHo in CUMS mice replicated previous discoveries in patients with depression. Intriguingly, MXYS only normalized several limbic regions, which suggests the essential roles of these regions in mediating the antidepressant effects of MXYS. Our results provide a reliable framework for the use of ReHo analysis with animal models of depression and further suggest a new perspective to elucidate the antidepressant effects of MXYS.